Exploring the relationship between short-term borrowings and profitability in China: the moderating role of cash conversion cycle - Mahmood, Faisal; Dongping, Han; Ahmed, Zahoor; Shahzad, Umeair; Ali, Nazakat; Bodian, Wang; Shahbaz, Muhammad (Journal of Business Economics and Management, 2021)
This study focuses on the moderating role of the cash conversion cycle (CCC) and its components while investigating the relationship between short-term borrowings and profitability in Chinese firms. The generalized method of moments (GMM) approach is employed on the panel data over the period 2000 to 2017. The findings reveal a significant moderating role of CCC and its components in the short-term borrowings and profitability relationship. Specifically, the firms following a conservative strategy in CCC and its components, adopt the same strategy in the external financing which lies in the long-term borrowings. Consequently, such firms require less short-term borrowings compared to the full sample. However, the firms following an aggressive strategy in the CCC and its components, do not follow the aggressive strategy in external financing that lies in the short-term borrowings. Instead, these firms adopt the conservative strategy for profit maximization and require less amount of short-term borrowings compared to the full sample. Finally, several policy options are proposed to achieve the optimum relation between short-term borrowings and profitability.